HYDROXYAPATITE, ALGINATE, AND CHITOSAN FOR BONE SCAFFOLDS: SPECTROSCOPY STUDY: HIDROKSIAPATIT, ALGINAT, DAN KITOSAN SEBAGAI BAHAN SCAFFOLD TULANG: STUDI SPEKTROSKOPI - Milla, Lalita El (TALENTA, 2016)
Scaffolds is three dimensional structure that serves as a framework for bone growth. Natural materials are often used in synthesis of bone tissue engineering scaffolds with respect to compliance with the content of the human body. Among the materials used to make scafffold was hydroxyapatite, alginate and chitosan. Hydroxyapatite powder obtained by mixing phosphoric acid and calcium hydroxide, alginate powders extracted from brown algae and chitosan powder acetylated from crab. The purpose of this study was to examine the functional groups of hydroxyapatite, alginate and chitosan. The method used in this study was laboratory experimental using Fourier Transform Infrared (FTIR) spectroscopy for hydroxyapatite, alginate and chitosan powders. The results indicated the presence of functional groups PO43-, O-H and CO32- in hydroxyapatite. In alginate there were O-H, C=O, COOH and C-O-C functional groups, whereas in chitosan there were O-H, N-H, C=O, C-N, and C-O-C. It was concluded that the third material containing functional groups as found in humans that correspond to the scaffolds material in bone tissue engineering.